Annual reports on NMR spectroscopy. Volume 17 - Webb, G. A. (Graham Alan), 1935-; ScienceDirect eBooks (Orlando ; London : Academic Press, 1986)
NMR spectroscopy has grown to be a vitally important technique with applications in many areas of science. Annual Reports on NMR Spectroscopy is quickly becoming the source for the latest information on current progress, both experimental and theoretical. Chemists in a variety of disciplines will be interested in this up-to-date, comprehensive series.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Nuclear magnetic resonance spectroscopy; Nuclear spectroscopy; Nuclear magnetic resonance spectroscopy; Nuclear spectroscopy; Electronic books